TECHNOLOGY OF DEVELOPMENT OF ARTISTIC AND AESTHETIC COMPETENCE OF STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, the technology for developing artistic and aesthetic competence of future visual arts teachers is improved based on today's demand and based on a creative approach. To date, the problem of technological development of students' artistic and aesthetic competence has been studied by many research scientists. For example, scientists of the CIS V. Maksimova, L. Klikova, R. Djandosov, research scientists of our country F. Rabbimova, N. Yuldasheva put into practice various technologies of developing artistic and aesthetic competence of students. The characteristic aspects of artistic and aesthetic education technologies are manifested in the joint implementation of research activities in educational subjects. As a result of emotional-imagery, discussion and choice, strong interpersonal cooperative action is created. The technologies used in the process of artistic-aesthetic education are designed to develop the artistic-aesthetic competences of students, and as a result of ensuring democratic relations between the teacher and students, the quality and efficiency of artistic-aesthetic education is achieved. Taking into account these aspects, in this article, a four-stage (motivational, cognitive, practical-active, personal-developing) pedagogical algorithm of the technology of developing the artistic aesthetic competence of future visual arts teachers has been developed. methods and means of using technology in the educational process are highlighted